Answer:
FH=39
Explanation:
FGH~KJH
GH=x+8
FH=4x-25
JH=32
KH=52
(these are the measurements I have)
x+8 / 32 = 4x-25 / 52
(cross multiply)
52(x+8) = 32(4x-25)
52x+416 = 128x-800
(subtract the 52x from the 128x)
416 = 76x-800
(add the 800 to the 416)
1216 = 76x
(divide the 76 over the 1216)
x = 16
(now plug x into FH)
FH = 4x-25
FH = 4(16)-25
FH = 39
(hope this helped)
FH =KH if triangle FJH and KJH is congruent
If two triangles FJH and KJH as shown n figure is congruent if,
FJ = KJ,
FH =KH and
JH =JH common
Triangle is congruent by SSS theorem
Therefore FH =KH
5.6m questions
7.3m answers